The design, development and vibration analysis of a high-speed aerostatic bearing - Frew, David Anthony (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.